Behaviour drives contemporary evolution in a failing insect-parasitoid importation biological control programme - Shields, Morgan W.; Wratten, Steve D.; Van Koten, Chikako; Phillips, Craig B.; Gerard, Philippa J.; Goldson, Stephen L. (Frontiers in Ecology and Evolution, 2022)
Biological control of pests continues to become more important in agriculture as pesticides are being withdrawn. However, successful control can be compromised by contemporary evolution. Recent work in New Zealand has shown that the once-successful biological control programme of the sexually-reproducing grassland weevil pest Listronotus bonariensis by the asexual parasitoid Microctonus hyperodae has now failed. In order to explain the mechanisms associated with this, weevil parasitism rates were intensively monitored between 1994 and 2019. Frequent sampling took place at widely-dispersed New Zealand sites spanning the warmer northern regions to the cooler south. Based on elapsed heat accumulation above the parasitoid’s development temperature threshold of 10.2oC (DD), the results over c. 25 years indicated that the extent of parasitism decline at a given location was directly related to the accumulated DD. The latter, in turn, was taken to be indicative of parasitoid activity and selection pressure. Accordingly, laboratory microcosm experiments measuring the response of weevils collected from the North-South distribution to a common population of parasitoids, showed that the weevils from the warmer northern region showed higher rates of avoidance of the searching parasitoids than those from the cooler south. This strongly supported the hypothesis that the weevil resistance mechanism is related to levels of parasitoid avoidance behaviour arising from long-term parasitoid selection pressure. This study of the behaviourally-based acquisition of resistance to a biological control agent illustrates a general need to consider the potential capability of a exotic target host to develop resistance to imported biological control agents. This includes identifying existing host adaptations that selection pressure could potentially act upon that may compromise otherwise successful biological control programmes. Such a requirement points to the need for long-term monitoring of biological control systems and understanding of parasitoid/host dynamics.